KOHESI LEKSIKAL REITERASI DALAM BUKU DONGENG NUSANTARA 33 PROVINSI DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Putri, Shely Nasya (JURNAL PESONA, 2016)
This study aims to describing the lexical cohesion reiterasi in the Buku DongengNusantara 33 Provinsi and its implications for learning Indonesian at junior highschool. The data in this study is the text contained in the Buku Dongeng Nusantara 33Provinsi numbered 39 text. The result shows that the use lexical marker reiterasidivided into two, repetition and hyponymy. Reiterasi divided into three types, namely afull replay, replay another form, and repeat with the replacement / synonyms.Repetition in the form replicates another form is divided into replicates other formsthat have the same basic shape and replicates other forms that have the samereference. Repetition in the form of synonyms divided by shades of meaning, iesynonyms based on additional meaning, value sense (emotive), and the prevalence ofthe use of the lexeme.Keyword: lexical cohesion, reiterasi, folktale.